Methyl NFSI: atom-economical alternative to NFSI shows higher fluorination reactivity under Lewis acid-catalysis and non-catalysis. Issue 7 (1st December 2015) - Fukushi, Kazunobu; Suzuki, Satoru; Kamo, Tomohiro; Tokunaga, Etsuko; Sumii, Yuji; Kagawa, Takumi; Kawada, Kosuke; Shibata, Norio
Abstract : Me-NFSI is more effective for the fluorination of active methines under Lewis acid-catalysis and non-catalysis than NFSI. Abstract : Me-NFSI was first reported in 1994. Despite its atom-economical structure and similarity to a well-explored fluorinating reagent, NFSI, Me-NFSI has not appeared in the literature in over 20 years. We disclose that Me-NFSI is more effective for the fluorination of active methines under Lewis acid-catalysis and non-catalysis than NFSI.